2012
DOI: 10.6061/clinics/2012(01)06
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of hypoxia-inducible factor-1α (HIF-1α) expression by interleukin-1β (IL-1β), insulin-like growth factors I (IGF-I) and II (IGF-II) in human osteoarthritic chondrocytes

Abstract: OBJECTIVE:Hypoxia-inducible factor 1 alpha regulates genes related to cellular survival under hypoxia. This factor is present in osteroarthritic chondrocytes, and cytokines, such as interleukin-1 beta, participate in the pathogenesis of osteoarthritis, thereby increasing the activities of proteolytic enzymes, such as matrix metalloproteinases, and accelerating cartilage destruction. We hypothesize that Hypoxia Inducible Factor-1 alpha (HIF-1α) can regulate cytokines (catabolic action) and/or growth factors (an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 30 publications
1
39
0
1
Order By: Relevance
“…Recently, it has been shown that the expression of HIF-1α can be upregulated not only by hypoxia, but also by other nonhypoxic factors, such as the inactivation of tumor-suppressor genes (p53, pVHL, and PTEN [35,36,37]), activation of some viral oncoproteins (EBV and HPV-16 [38,39]), and challenge by IGF-I [40,41,42], etc. In the present study, the human NSCLC cell line A549 was used to investigate the effect of EGCG on the IGF-I-induced HIF-1α and VEGF expression and the proangiogenic activity of human lung cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been shown that the expression of HIF-1α can be upregulated not only by hypoxia, but also by other nonhypoxic factors, such as the inactivation of tumor-suppressor genes (p53, pVHL, and PTEN [35,36,37]), activation of some viral oncoproteins (EBV and HPV-16 [38,39]), and challenge by IGF-I [40,41,42], etc. In the present study, the human NSCLC cell line A549 was used to investigate the effect of EGCG on the IGF-I-induced HIF-1α and VEGF expression and the proangiogenic activity of human lung cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Insulin-like growth factor 1, for instance, augmented the accumulation of HIF1A in normoxia in several cell types (Alam et al 2009, Sartori-Cintra et al 2012, Yu et al 2012. Reactive oxygen species (ROS) is another factor implicated in HIF1A accumulation.…”
Section: Introductionmentioning
confidence: 99%
“…IL-17 can also promote bone resorption and collagen degradation; enhance the expression of chondrocytes MMP-9, MMP-13 and other metal matrix proteases; strengthen cartilage plate destruction and cartilage tissue decomposition; and induce joint destruction [69,70]. Studies have shown that IL-17 can enhance the formation of blood vessels in arthritic cartilage while activating and increasing vascular endothelial growth factor, aggravating in ammation, and causing bone brosis and hyperplasia [71]. Moreover, clinical studies have shown that the expression level of IL-17 in OA synovium and synovial uid is increased, and the increase in IL-17 level in OA synovial uid is related to the severity of OA [72][73][74].…”
Section: Discussionmentioning
confidence: 99%